Is 3-Dimensional Scanning Really Helpful in Implant-Based Breast Reconstruction?: A Prospective Study. (March 2022) - Huang, Dun-Wei; Chou, Yu-Yu; Liu, Hung-Hui; Dai, Niann-Tzyy; Tzeng, Yuan-Sheng; Chen, Shyi-Gen
Abstract : Background: Breast reconstruction is an integral part of breast cancer treatment, and implant-based breast reconstruction is the most commonly used method worldwide. However, there is still no technique that allows surgeons to predict the volume of the required implant. Although computed tomography and magnetic resonance imaging provide adequate representations of the breast, these procedures are time-consuming, expensive, and expose patients to radiation. Therefore, there is a need for safer, noninvasive alternatives for preoperative breast volume measurements. Patients and Methods: This study is a prospective review of 12 patients with early-stage breast cancer who underwent nipple-sparing mastectomy and immediate breast reconstruction with implants. Preoperatively, the Artec Eva 3D scanner was used to acquire volumetric measurements of the breasts. Intraoperatively, the volume of the mastectomy specimen was measured using the water displacement method. Correlations among the preoperative breast, mastectomy specimen, and estimated and final implant volumes were analyzed through Pearson correlation coefficient. A correction prediction factor of 85% was applied where necessary. Patient and physician satisfaction were evaluated 3 months postoperatively. Results: Our study found a statistically significant correlation between the preoperative breast volumes measured by the Artec Eva 3D scanner and intraoperative mastectomy specimen volumes ( r = 0.6578). There was no correlation between the preoperative breast volumes and final implant volumes, mastectomy specimen volumes and final implant volumes, and estimated implant volumes and final implant volumes. Conclusions: Although the Artec Eva 3D scanner can offer relatively accurate measurement of breast volumes, multiple studies still need to be done to determine how these data can be applied to the mastectomy procedure and breast implant selection. It may be more applicable for preoperative planning in breast augmentation surgery. Future surgeons should also take into account that variabilities in natural breast size, tumor size, cancer stage, and in patient and physician preferences all influence the outcome of breast reconstruction surgery.